PENGARUH PENENTUAN HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN OJEK ONLINE GRAB DI KOTA PAREPARE - Hardi, Humaida; Handayani, Sri Reski; Sudirman, Sudirman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of pricing and service quality on consumer satisfaction of ojek online Grab in Parepare City (Case Study in Ujung District). The data collection techniques used in this study were questionnaires, observations, and literature studies. The sample in this study amounted to 147 respondents. The data analysis technique in this study used multiple linear regression analysis with the help of a computerized system (computer program IBM Statistics SPSS 26). The results of the study indicate that partially Pricing (X1) has a positive and significant effect on Consumer Satisfaction (Y). Partially, Service Quality (X2) has a positive and significant effect on Consumer Satisfaction (Y). Simultaneously, Pricing and Service Quality have a positive and significant influence on Consumer Satisfaction.